Faktor-Faktor yang Memengaruhi Implementasi SAK di UMKM Gudeg Daerah Istimewa Yogyakarta - Dewanto, Devi Aulia Rahma; Herwiyanti, Eliada; Ramadhanti, Wita (Soedirman Accounting, Auditing and Public Sector Journal, 2022)
This study aims to determine the effect of education level, understanding of accounting, information technology, and business size on the implementation of SAK on MSMEs Gudeg in the Special Region of Yogyakarta. The population in this study is the Gudeg MSME actors in the Special Region of Yogyakarta who are registered in the GrabFood application, totaling 88 business actors. Sampling by purposive sampling method was carried out through several criteria, in order to obtain 45 targeted MSMEs. The data analysis technique is through multiple linear regression analysis. Of the 4 hypotheses proposed, there are 2 accepted hypotheses and 2 rejected hypotheses. The accepted hypotheses are H2 and H3, namely accounting understanding has a positive effect on the implementation of SAK on MSMEs and information technology has a positive effect on SAK implementation on MSMEs. While the rejected hypotheses are H1 and H4, with the result that the level of education has no effect on the implementation of SAK on MSMEs and business size does not affect the implementation of SAK on MSMEs. The results of this research show that along with the existing developments, access to compiling financial reports is easier due to an understanding of accounting and information technology which no longer depends on the level of education and the size of the business. This research is expected to be a reference for MSME actors as well as policy makers so that effectiveness in efforts to implement SAK on MSMEs can be carried out, mainly by increasing accounting understanding and the use of information technology.